KEPASTIAN HUKUM PEMBIAYAAN MUSYARAKAH PADA PERBANKAN SYARIAH TERKAIT EKSISTENSI UTANG ANTARA NASABAH DAN BANK - Anindya Shamara Arminawan; Yuhelson, Yuhelson; Erny Kencanawati (Bajang Institute, 2025)
Musyarakah is a cooperative agreement between two or more people to carry out a certain business, where each party contributes to funds or charity with the agreement that the profits or risks will be shared together in accordance with the initial agreement. The formulation of the problem in this study is how the existence of debt between customers and banks related to musyarakah financing in Islamic banking followed by debt recognition and how to realize legal certainty related to customers and banks related to musyarakah financing in Islamic banking. The theories used in this research are the theory of legal certainty and sharia banking theory.The research method used is the normative juridical approach method supported by empirical, namely research conducted based on the main legal material by examining theories, concepts, legal principles, applicable laws and regulations and other information related to this research.Musyarakah is a form of cooperation or partnership financing, so there is no existence of debt and credit between the customer and the bank in this financing. However, debt can be formed if the customer makes a default, namely not fulfilling the things that have been agreed in the contract. This is regulated in PSAK 106 where all customer obligations related to the financing in the Bank's books will be transferred as debt. Based on the research, financing with a musyarakah contract is accompanied by a debt clause or debt acknowledgment contained in the standard contract prepared by the bank. With this debt recognition clause, the essence of the musyarakah contract can change from being a cooperation contract to a debt and credit contract and there will be debt existence from the beginning of the contract. However, the inclusion of the debt acknowledgment clause cannot be said to deviate from the provisions because the Financial Services Authority (OJK) Regulation stipulates that banks are allowed to make a letter of acknowledgment of receipt of business funds and a letter of acknowledgment of obligation to return the business funds.